Analysis of mediation effect of country-of-origin image on brand equity. (27th March 2019) - Jain, Vishal; Bariar, Shalini
Marketers are required to study consumer psyche for the development of sustainable competitive advantage over other brands. One of the most significant challenges for marketing professionals is the ability to create, maintain and enhance brand equity, as it is the most critical indicator of the product performance. The purpose of this research is to investigate a theoretical framework in which brand's country-of-origin image is suggested to influence the level of brand equity of hair care products. It also studies the mediation effects of various dimensions of brand equity, which are brand loyalty, brand awareness, brand association and perceived quality. The study shows that in the absence of mediators the country-of-origin image has a positive and significant effect on brand equity. However, in the presence of mediators the relationship becomes insignificant, which confirms the mediation effect. The present study will be useful to create the right message for the target customers.